Ben Highmore: The Great Indoors. At Home in the Modern British House - Jaine, Tom (Petits Propos Culinaires, 2014)
Ben Highmore: The Great Indoors. At Home in the Modern British House: Profile, 2013: 292 pp., hardback, £15.99.